Aggravation of Cardiovascular and Respiratory Decline in Advanced Duchenne Muscular Dystrophy Complicated by Dilated Cardiomyopathy - Case Study and Review of Literature - Iwona Welian-Polus; Bartosz Mazur; Michał Bielak; Magdalena Mazur; Elżbieta Rypulak; Wiktoria Wilanowska; Anna Greguła; Karol Stachyrak; Dawid Mika; Kamila Turek (Kazimierz Wielki University, 2024)
Introduction: Duchenne muscular dystrophy is a genetic X-linked recessive disorder. This condition is characterized by progressive loss of muscle tissue. Thus, it results in deterioration and inability to perform basic motor skills such as independent movement or breathing. Due to progressive muscle weakness, patients with advanced stages of DMD require mechanical ventilation, feeding, and rehabilitation. Furthermore, alterations in cardiac muscle lead to cardiomyopathy. Despite advanced supportive treatment, DMD is a fatal disease. Purpose: The aim of the paper is to present, using a case study description, the current standards of treatment for patients with Duchenne muscular dystrophy as well as the current state of knowledge and new discoveries regarding this medical condition. Material and methods The patient's medical records were analyzed and available literature in PubMed was reviewed to write this article using the keywords: "Duchenne muscular dystrophy"; "cardiomyopathy"; "mechanical ventilation"; "gene therapy"; Conclusions Early detection of respiratory and circulatory insufficiency improves the patient's quality of life. Many patients with an advanced stage of Duchenne muscular dystrophy need specialized treatment, for example, in the intensive care unit. Therefore there is an urgent need for new treatment methods, such as gene therapies, which can slow down or break the course of the disease. New discoveries and the implementation of new treatment standards can enhance the quality of life for patients and extend their lifespans.